2011
DOI: 10.3406/ecmed.2011.1335
|View full text |Cite
|
Sign up to set email alerts
|

La surveillance à long terme des écosystèmes arides méditerranéens : quels enseignements pour la restauration ? Cas d’une steppe d’Alfa (Stipa tenacissima L.) en Algérie

Abstract: La désertification des parcours pastoraux steppiques arides constitue une des problématiques fondamentales de développement dans le sud de la Méditerranée. Elle pose avec acuité les questions de restauration et de gestion de ces écosystèmes qui ont été, dans la plupart des cas, soumis au surpâturage depuis des décennies. Divers modèles ont été développés pour expliquer la dynamique des écosystèmes arides dont l’origine, les causes et les mécanismes des changements sont souvent peu ou pas connus. Le suivi à lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…These measures are based on techniques that allow the degraded rangelands to rest for a period of time, ranging from three to five years under normal conditions, in order to enhance the regeneration of the vegetation cover and to ameliorate the pastoral productivity of these rural spaces. The beneficial effect of this technique has been confirmed by several studies conducted in different Algerian regions (Aidoud, Slimani, & Rozé, 2011;Amghar, 2002;Amghar & Kadi-Hanifi, 2008;Amghar, Kadi-Hanifi, & Sadji, 2005;Khalid, Benabdeli, & Morsli, 2015;Salemkour, Aidoud, Chalabi, & Chefrour, 2016;Slimani, Aidoud, & Rozé, 2010;Yahiaoui, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…These measures are based on techniques that allow the degraded rangelands to rest for a period of time, ranging from three to five years under normal conditions, in order to enhance the regeneration of the vegetation cover and to ameliorate the pastoral productivity of these rural spaces. The beneficial effect of this technique has been confirmed by several studies conducted in different Algerian regions (Aidoud, Slimani, & Rozé, 2011;Amghar, 2002;Amghar & Kadi-Hanifi, 2008;Amghar, Kadi-Hanifi, & Sadji, 2005;Khalid, Benabdeli, & Morsli, 2015;Salemkour, Aidoud, Chalabi, & Chefrour, 2016;Slimani, Aidoud, & Rozé, 2010;Yahiaoui, 2012).…”
Section: Introductionmentioning
confidence: 71%
“…This indicates that the exclosure technique has not the same impact on ephemeral plants and perennial ones. In other study sites, where the effect of exclosure on floristic composition in S. tenacissima stands was studied, the disappearance of perennials was accompanied by an increase in ephemeral cover, biomass and species richness in the unprotected areas, especially following the long‐term degradation caused by overgrazing and drought (Aidoud et al, ; Slimani et al, ). This phenomenon, known in North Africa as “therophytisation phenomenon,” is considered by some authors to be a severe desertification level (Daget, ; Quézel, ) that can occur in our study site, although, to verify this, species richness between the treatments needs to be exhaustively compared.…”
Section: Discussionmentioning
confidence: 97%
“…The first approach clearly shows the benefit offered by a period of livestock exclusion on vegetation features especially on perennial species. The decrease of the perennial plants cover and biomass in grazed area is due to the disappearance of the S. tenacissima , which is overgrazed during periods of low vegetation growth (summer and winter) when the ephemerals disappear, or during successive periods of low annual rainfall (Aidoud, Slimani, & Rozé, ; Slimani et al, ). In contrast, the difference between the treatments regarding the cover and biomass of ephemerals was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, long-term grazing causes slow and continuous changes in both vegetation and soil, inducing persistent land degradation of the ecosystem (Porensky et al, 2016). In the steppes of West Algeria, Aidoud et al (2011) observed a decrease in the level of clay of 57% and in SOM of 61% in steppes grazed for 30 years, while the decrease was not significant for the two soil variables in steppes with grazing exclusion. The long-term degradation of the Halfa steppe was accompanied by severe deterioration of edaphic properties.…”
Section: Discussionmentioning
confidence: 94%